ТЕПЛОВИЙ РОЗРАХУНОК СУХИХ ТРАНСФОРМАТОРІВ З ЛИТОЮ ІЗОЛЯЦІЄЮ ТА З ФОЛЬГОВИМИ ОБМОТКАМИ - Іванков, В.Ф.; Басова, А.В. (Інститут електродинаміки Національної академії наук України, 2024)
The method of analytical thermal calculation of dry transformers with cylindrical conductors with cast insulation and foil windings is presented. The surface and volume averaged temperatures of the magnetic system core and the windings are determined from the one-dimensional non-linear substitute thermal circuit of the transformer. To clarify the temperature distribution across the cross-section of the anisotropic foil winding, the solution of the boundary value problem in the form of a two-dimensional Poisson equation with heat transfer coefficients calculated from the substitute scheme is used. Calculation example of a dry transformer with a capacity of 2500 kVA is given. Numerical CFD modeling was performed to verify the calculation results. Bibl. 10, fig. 9, tab. 3.